Ответы и объяснения

2013-06-16T04:01:08+00:00

Функции сложные, поэтому немного теории перед нахождением их производных:

 

(u-v)'=u'v-uv'\\ (cx)'=c\\ (\frac{u}{v})'=\frac{u'v-uv'}{v^{2}}\\ (\sqrt{x})'=\frac{1}{2\sqrt{x}}\\ (cosx)'=-sinx\\ (u^{n})'=n\cdot u^{n-1}\cdot u'\\

 

 

1. </span>f (x) = 4x - \frac{2}{\sqrt{x}}\\ f' (x) = (4x - \frac{2}{\sqrt{x}})' = {4x}'-(\frac{2}{\sqrt{x}})'=4 - \frac{2' \cdot \sqrt{x}-2\cdot (\sqrt{x})'}{(\sqrt{x})^{2}}=\\ =4 - \frac{-2\cdot \frac{1}{2\sqrt{x}}}{(\sqrt{x})^{2}}=4 - (- \frac{\frac{1}{\sqrt{x}}}{(\sqrt{x})^{2}})=4 + \frac{1}{\sqrt{x}}:\frac{(\sqrt{x})^{2}}{1}=4+\frac{1}{\sqrt{x}}\cdot \frac{1}{x}=\\ =4+\frac{1}{\sqrt{x^{3}}}<span>

 

2. y = cos^{2}x\\ y' = (cos^{2}x)'=2\cdot cosx \cdot (- sinx)=-2cosx\cdot sinx\\